2023
DOI: 10.1021/acs.est.2c09299
|View full text |Cite
|
Sign up to set email alerts
|

Acrolein Exposure Impaired Glucose Homeostasis and Increased Risk of Type 2 Diabetes: An Urban Adult Population-Based Cohort Study with Repeated Measures

Abstract: Acrolein is an identified high-priority hazardous air pollutant ubiquitous in daily life and associated with cardiometabolic risk that attracts worldwide attention. However, the etiology role of acrolein exposure in glucose dyshomeostasis and type 2 diabetes (T2D) is unclear. This repeated-measurement prospective cohort study included 3522 urban adults. Urine/blood samples were repeatedly collected for determinations of acrolein metabolites (N-acetyl-S-(3-hydroxypropyl)-L-cysteine, N-acetyl-S-(2-carboxyethyl)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Previous evidence has shown that UFP is capable of transporting a wide range of hazardous materials, including transition metals, oxidizing gases, and organic compounds (Oberdorster 2001 ). All of these components have the potential to cause inflammation (Song et al 2023 ; Wang et al 2023 , 2022a ), which could induce and provoke respiratory diseases like COPD. Besides, other studies indicate that adverse respiratory effects associated with PM may also arise from the generation of reactive oxygen species and oxidative stress, which could case oxidant-mediated cellular damage to respiratory tract (Nel et al 2006 ) and could further impact innate and adaptive immunity (Liu et al 2023 ; Villegas et al 2014 ; Wang et al 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence has shown that UFP is capable of transporting a wide range of hazardous materials, including transition metals, oxidizing gases, and organic compounds (Oberdorster 2001 ). All of these components have the potential to cause inflammation (Song et al 2023 ; Wang et al 2023 , 2022a ), which could induce and provoke respiratory diseases like COPD. Besides, other studies indicate that adverse respiratory effects associated with PM may also arise from the generation of reactive oxygen species and oxidative stress, which could case oxidant-mediated cellular damage to respiratory tract (Nel et al 2006 ) and could further impact innate and adaptive immunity (Liu et al 2023 ; Villegas et al 2014 ; Wang et al 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…The definition of diabetes was based on the diagnostic criteria recommended by the American Diabetes Association. 16,17 Diabetes was defined as having at least one of the following conditions: (1) self-reported diabetes diagnosed by a physician, (2) using insulin or hypoglycemic drugs, (3) FPG ≥ 7.0 mmol/L, or (4) HbA 1 c ≥ 6.5%.…”
Section: Ascertainment Of Diabetesmentioning
confidence: 99%
“…Acetaldehyde exists in various plants, ripe fruits, and vegetables and is used to blend apple-type, citrus-type, and other flavors. Nevertheless, aldehydes are a strong irritant, corrosive, carcinogenic, allergenic, and have mutagenic effects. Excessive emission of aldehydes not only causes environmental pollution, but also leads to a series of serious health problems in the event of long-term exposure to a high aldehyde atmosphere. Currently, various strategies have been developed for detecting aldehydes, e.g., chromatography, , surface-enhanced Raman spectroscopy, electrochemical methods, and fluorescence methods . However, there are drawbacks, such as being time-consuming and having a high cost and a demanding operation.…”
Section: Introductionmentioning
confidence: 99%